Absolute configuration assignment of an unusual homoisoflavanone from Polygonum ferrugineum using a combination of chiroptical methods - Batista Jr., João Marcos (2015)
The absolute configuration of the homoisoflavanone 5,7-dihydroxy-6-methoxy-3-(9-hydroxy-phenylmethyl)-chroman-4-one (1), found in Polygonum species, has been determined as 3R,9R by using a combination of electronic and vibrational chiroptical spectroscopic methods. The experimental spectra were interpreted with the aid of density functional theory calculations. The risks of relying upon a single method for stereochemical characterization of natural products are discussed.